Epidemiological transition in Sri Lanka - Dissanayake, Lakshman (My University, 2000)
This paper attempts to discuss the changes in disease and death patterns in Sri Lanka by placing them in the context of the Epidemiologic Transition Theory and then examines how this transition is expected to affect present and future demographic and social patterns in the island. Sri Lanka's pattern of mortality before 1945 exemplifies the Age of Pestilence and Famine. Many of the peaks and high plateaus of mortality observed were due to the epidemics which recurred periodically throughout this period. The Age of Receding Pandemics commenced in the mid-1940s. Sri Lankan mortality breakthrough occurred during the 1946-53 period, adding over an additional decade to expectation of life at birth during that seven year period. The Age of Degenerative and Man-Made Diseases began in the 1970s. During this stage, it appears that degenerative diseases like heart diseases, cancer, stroke and diabetes become increasingly prominent. The epidemiologic transition in Sri Lanka affected demographic and social patterns in a variety of ways. The shift from infectious to degenerative diseases resulted in an increase in the average age at death. Also, the numbers of children increased as a result of the improved child survival, and there was a wave of children and youth moving up through the population pyramid. In the third stage of the transition, Sri Lankan population as anywhere else will become older because of declining fertility as well as the advancement of life expectancy. ' In addition, elderly population will be more feminized as a result of the improvement of female survival chances. Providing medical care will become increasingly more costly and complex, arising out of the need to acquire new technology to tackle problems of survival and aging. Also, the advice and services of other disciplines such as psychology, sociology, anthropology, and communication sciences, would become very necessary .
Keywords: Epidemiological transition in Sri Lanka